New Engine Simulation Structure Model Applied to SI Engine - Nekooei, Mohammad Javad; Koto, Jaswar (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2017)
High ratio emissions that outcome from incomplete combustion cause air contamination, poorer the performance of the spark ignition (SI) engine and raise fuel consumption. Uncompleted combustion emitted a high ratio of CO, HC, NOx and PM harmful emissions such as come into atmosphere. This study has reviewed existing engine simulation structures using different methods as s as follows Neural Networks (NN), Sliding Mode Control (SMC), Proportional-Integral (PI) Predictive Control (MPC) and DRNN- based MPC method. The existing engine models were compared with the new engine simulation structure model which was proposed by the authors, using Hybrid Fuzzy Logic Control (HFLC) method in term of AFR. The simulation engine model in Matlab/Simulink using new engine simulation has founded that AFR (15.02, 14.4) which closes to the stoichiometric value of 14.7 compared by using Neural Networks (NN) method, a Sliding Mode Control (SMC) method, a Proportional' Integral (PI) control method, Model Predictive Control (MPC) method and DRNN-based MPC method.